The Effect of MSME Growth and Economic Growth on The Unemployment Rate in South Sulawesi - Hairil, Hairil; Patra, I Ketut; Ikbal, Muhammad (MediaTrend, 2025)
This study aims to analyze the influence of Micro, Small, and Medium Enterprises (MSMEs) growth and economic growth on the unemployment rate in South Sulawesi Prov-ince for the 2013–2023 period. The method used is a quanti-tative approach with multiple linear regression analysis, us-ing secondary data obtained from the Central Statistics Agency, DISKOPUKM, and related agencies. The results of the study show that both partially and simultaneously, the growth of MSMEs and economic growth do not have a sig-nificant effect on the unemployment rate. Although both in-dicate a negative relationship direction, the effect is not sta-tistically significant. This shows that unemployment in South Sulawesi is more influenced by other factors such as labor quality, technology adoption, and labor policies. This re-search shows the need to strengthen the capacity of human resources and policies that support the productivity of MSMEs in order to contribute more to labor absorption.